2012
DOI: 10.1080/00071668.2012.745929
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects associated with high-dose acetylsalicylic acid and sodium salicylate treatment in broilers

Abstract: 1. Acetylsalicylic acid (ASA) and sodium salicylate (SS) are considered safe for poultry and often used in avian medicine. However, information on tolerance and specific side effects of these drugs in birds is lacking. 2. The aim of this study was to determine the effects of 14 d administration of high doses (200 or 400 mg/kg) of either ASA or SS on body weight gain, blood biochemistry, white and red blood cell counts and pathology in broilers. In addition, minimal plasma salicylate concentrations were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Unfortunately, lack of gentisic acid measurement in the present study as well as insufficient data on cytochrome P450 function in turkeys limit the possibility to confirm the autoinduction of salicylate metabolism as the process responsible for the biphasic elimination profile seen in this study. Although the underlying mechanism is not entirely clear, time‐dependent decrease in plasma salicylate concentration had been already observed during 2‐week daily administration with SS in broiler chickens (Poźniak et al., ) and in laying hens (Poźniak et al., ). In broilers, this effect has been associated with a dose‐dependent increase in the relative weight of liver which may support the hypothesis of metabolic induction (Poźniak et al., ).…”
Section: Pharmacokinetic Parameters (Median and Range) Of Salicylate mentioning
confidence: 95%
See 2 more Smart Citations
“…Unfortunately, lack of gentisic acid measurement in the present study as well as insufficient data on cytochrome P450 function in turkeys limit the possibility to confirm the autoinduction of salicylate metabolism as the process responsible for the biphasic elimination profile seen in this study. Although the underlying mechanism is not entirely clear, time‐dependent decrease in plasma salicylate concentration had been already observed during 2‐week daily administration with SS in broiler chickens (Poźniak et al., ) and in laying hens (Poźniak et al., ). In broilers, this effect has been associated with a dose‐dependent increase in the relative weight of liver which may support the hypothesis of metabolic induction (Poźniak et al., ).…”
Section: Pharmacokinetic Parameters (Median and Range) Of Salicylate mentioning
confidence: 95%
“…Although the underlying mechanism is not entirely clear, time‐dependent decrease in plasma salicylate concentration had been already observed during 2‐week daily administration with SS in broiler chickens (Poźniak et al., ) and in laying hens (Poźniak et al., ). In broilers, this effect has been associated with a dose‐dependent increase in the relative weight of liver which may support the hypothesis of metabolic induction (Poźniak et al., ). Verification of this hypothesis requires further studies.…”
Section: Pharmacokinetic Parameters (Median and Range) Of Salicylate mentioning
confidence: 95%
See 1 more Smart Citation
“…There is, however, evidence that during repeated administration of SS, the pharmacokinetics of SA in chickens undergoes significant changes that were never before observed in other species. In our earlier study, we have observed that the trough concentration of SA in chickens during two-week daily administration of ASA or SS had gradually decreased [ 10 ]. Since minimal plasma SA concentration was the only pharmacokinetic parameter investigated in this study, it seemed necessary to provide a more complete pharmacokinetic description of this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, não restam dúvidas de que mais estudos devam ser realizados para o melhor entendimento deste resultado, o qual pode estar inclusive relacionado à inferir que as doses empregadas não promoveram melhoria no desempenho dos frangos, já que os resultados dos grupos tratados se mostraram semelhantes aos do grupo controle. Na literatura, os índices de desempenho das aves suplementadas com salicilatos têm sido controversos Poźniak et al (2012). mostraram em seus estudos que houve diminuição do GP de ambos os grupos de aves tratados com AAS e SS de forma dosedependente quando as doses de 200 mg/kg e 400 mg/kg foram administradas por gavage durante 14 dias.…”
unclassified